2006
DOI: 10.1089/jpm.2006.9.1059
|View full text |Cite
|
Sign up to set email alerts
|

Errors in Symptom Intensity Self-Assessment by Patients Receiving Outpatient Palliative Care

Abstract: Vigilance needs to be maintained about the ESAS scores done by the patients particularly for symptoms of sleep, appetite, and pain. There is a likelihood of error if doctors or nurses do not routinely check the way patients have completed the assessment form. More research is needed to determine the best way to teach patients how to minimize errors in self-reporting of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 22 publications
3
61
0
9
Order By: Relevance
“…Some participants, however, lacked sufficient knowledge in the interpretation of certain symptoms, particularly tiredness, drowsiness, shortness of breath, well-being, and appetite. Reported benefits of the tool mainly related to direct patient care (symptom monitoring, treatment planning, communication); however, the tool was also useful for administrative and These findings suggest that the interpretation of symptoms is potentially problematic, not only for patients, as previously reported in the literature [9,20,21,23,24], but also for HCPs. Study participants provided many valid descriptions for explaining symptoms to patients, illustrating the complex multidimensional nature of most symptoms [22].…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Some participants, however, lacked sufficient knowledge in the interpretation of certain symptoms, particularly tiredness, drowsiness, shortness of breath, well-being, and appetite. Reported benefits of the tool mainly related to direct patient care (symptom monitoring, treatment planning, communication); however, the tool was also useful for administrative and These findings suggest that the interpretation of symptoms is potentially problematic, not only for patients, as previously reported in the literature [9,20,21,23,24], but also for HCPs. Study participants provided many valid descriptions for explaining symptoms to patients, illustrating the complex multidimensional nature of most symptoms [22].…”
Section: Discussionsupporting
confidence: 54%
“…We also considered concerns that were identified by patients in a think aloud study of the ESAS, in which they reported difficulties in interpretation of six of the nine symptoms [20]. The survey consisted of five sections: To assess HCP knowledge of the ESAS (Part 3), we examined the following three areas, which had previously been identified as problematic by patients [9,20]:…”
Section: Survey Designmentioning
confidence: 99%
See 2 more Smart Citations
“…More than 130 relevant articles and abstracts were identified, of which thirty-nine were primary studies published as complete peer-reviewed papers, representing 25 different institutions. Of the thirty-nine papers, thirteen were from Canada 6,11,[20][21][22][23][24][25][26][27][28][29][30] ; eight were from the United States [12][13][14]18,[31][32][33][34] ; eight were from Scandinavia (Sweden 15,[35][36][37] , Denmark [38][39] , Norway 40 , Finland 16 ); two were from Western Europe (Netherlands 41 , United Kingdom 42 ); five were from southern Europe (Switzerland 43 , Italy 17,[44][45][46] ); two were from Australia 47,48 ; and one was from Asia 49 .…”
Section: Methodsmentioning
confidence: 99%